EVALUASI PELAKSANAAN PRINSIP ATURAN HUKUM, TRANSPARANSI DAN AKUNTABILITAS PENGELOLAAN DANA KAMPANYE PEMILIHAN KEPALA DAERAH SERENTAK TAHUN 2020 - Lara Indah Yandri; Roby Hadi Putra; Putyanto Putyanto (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Evaluation of campaign fund management is very important in regional head elections, good management of campaign funds can determine victory in the 2020 regional head election. To carry out elections for regional heads with integrity, of course, you must use the principles of the rule of law that are transparent and accountable, so that the 2020 Pilkada can run the principle of justice in accordance with the principles of the election. This paper uses qualitative methods with secondary data to report results by using case literature studies, existing laws and theories and using SWOT analysis through the stages of data processing, data analysis, data reduction and drawing conclusions. The results of this study indicate that the strategy in implementing the rule of law, transparency and accountability in managing campaign funds is (1) the principles of rule of law have not been implemented optimally in managing campaign funds in regional head elections. (2) the implementation of the principle of transparency has not been effective in managing campaign funds in regional head elections. (3) and the ineffective implementation of the principle of accountability in managing campaign funds in regional head elections.Keywords: Rule of Law, Transparency, Accountability, Management of Campaign Funds